Effects of the Number of Neoadjuvant Cycles and Addition of Adjuvant Chemotherapy on the Prognosis of Muscle‐Invasive Bladder Cancer Treated With Radical Cystectomy - Shingo Hatakeyama; Rikiya Taoka; Jun Miki; Ryoichi Saito; Wataru Fukuokaya; Yoshiyuki Matsui; Takashi Kawahara; Ayumu Matsuda; Taketo Kawai; Minoru Kato; Tomokazu Sazuka; Takeshi Sano; et al. (Cancer Medicine, 2025)
ABSTRACT Objective To evaluate the effects of the number of neoadjuvant chemotherapy (NAC) cycles and the addition of adjuvant chemotherapy (AC) after NAC on overall survival (OS) of patients with muscle‐invasive bladder cancer (MIBC). Patients and Methods We retrospectively evaluated 1687 patients with cT2‐4NxM0 MIBC who received radical cystectomy (RC) alone or RC plus perioperative chemotherapy at 36 institutions within the Japanese Urological Oncology Group. We evaluated the effect of the number of NAC cycles (2 vs. ≥ 3 cycles) and the addition of AC on OS. Results Among the 1687 patients analyzed, 946 received a median of three NAC cycles. The pathologic complete response rate did not significantly differ between those who received 2 (22.9%) and ≥ 3 cycles (27.5%, p = 0.112). Moreover, no significant difference in OS was observed between the groups (p = 0.559). Multivariable Cox regression analysis showed that pathologic high‐risk (ypT2–4, pT3–4, or pN+) or cisplatin ineligibility were significantly associated with poor OS but not the number of NAC cycles (p = 0.238). We identified 942 pathologically high‐risk patients after RC who were eligible for AC. Notably, no significant OS improvement was observed with the addition of AC as intensive perioperative chemotherapy after NAC. The primary limitation was selection bias from confounding by clinical indication. Conclusions Our findings showed that three or more NAC cycles and the addition of AC may have limited effects on OS in MIBC patients who received RC.